Exergy analysis of development on supercritical CO2 solar Rankine cycle system with thermally driven pump. Issue 1 (1st January 2018) - Pumaneratkul, Chayadit; Horino, Takashi; Yamasaki, Haruhiko; Yamaguchi, Hiroshi
Abstract: The innovative development of a thermally driven pump in the supercritical CO2 solar Rankine cycle system has been carried out and investigated to increase the system efficiency in field operation. To confirm the advantage of the thermally driven pump over conventional mechanical feed pump, the energy and exergy analysis of the system is investigated and discussed. It can be confirmed from the analysis that the thermally driven pump operating under an actual climate condition gives the higher exergetic efficiency in output power to the system compared with the mechanical feed pump. On the contrary, the high rate of exergy destruction is found in the evacuated solar collector under both system conditions. To increase the exergetic efficiency and to prevent the destruction rate, the proper components design, which can be considered as the essential factor to develop the higher performance system, are suggested in the present study.